Which countries bid for the Olympic Games? - Maennog, W.; Vierhaus, C. (Hamburg Contemporary Economic Discussions, 2016)
This contribution analyzes 132 factors on their potential to discriminate countries bidding for hosting the Olympic Games from non-bidding countries. Our binary, clustered model using generalized estimating equations (GEE) shows that countries recording long-term economic growth and pursuing a liberalization and globalization policy will consider an Olympic bid. In addition, countries with an urban population above 10 million, with stable election results and an improvement in health standards as well as more attractive tourism destinations are more likely to bid for the Olympic Games. Finally, the bid decision is shaped by experience in hosting major sports events, a country and regional rotation, persistence and climatic conditions.